El Padre Andrés Marcos Burriel y la procedencia de CIL II 2323 Y CIL II 2324 - Hernando Sobrino, María del Rosario (Gerión. Revista de Historia Antigua, 2008)
The aim of this paper is to explain the reasons for the removal of CIL II 2323 and CIL II 2324 from the epigraphic group of Carbula (Almodóvar del Río, Córdoba) and their relocation to the corpus of Cuenca’s province. A. M. Burriel, the Jesuit who saw and described these tombstones in 1745, specifies that both of them were indeed found in Almodóvar del Pinar (Cuenca).